Influence of Hindu Religious Beliefs and Cultural Values on Non-Hindu/Indigenous Students in a School of Post-Secular Nepal - Rai, Indra Mani; Rai, Dipak Raj (Journal of Nepalese Studies, 2025)
This paper examines the influence of Hindu religious beliefs and cultural values on non-Hindu/Indigenous students through the institutionalization of particular rituals and festivals (the recitation of Saraswati Vandana and the celebrations of Saraswati Puja, Guru Puja, and Holi) within Nepal’s public education system. Based on the critical ethnographic method in one of Kathmandu’s oldest public schools, the study shows the Hindu rituals and festivals that are actively celebrated in school are taken as normative school culture in the post-secular context of Nepal. Applying Bourdieu’s ideas of cultural reproduction and symbolic violence, the analysis reveals that the school legitimizes Hindu values as common while marginalizing non-Hindu and Indigenous students. Teachers, positioned as “gurus” under the Hindu notion of Guru Bhakti, reinforce hierarchical teacher–student relationships that discourage critical thought and promote values such as obedience and loyalty towards teachers. Such practices reproduce socio-cultural and religious hierarchies within the school, legitimizing Hindu dominance. Consequently, the school, supposed to be a secular and inclusive institution functions as a mechanism of subtle Hinduisation and symbolic violence against non-Hindu/Indigenous students. The study concludes that the school perpetuates privileging students from dominant religious and cultural groups and marginalizes diverse non-Hindu and Indigenous groups. Thus, there is an urgent need for educational reform that recognizes the religious and cultural diversity and promotes equity and inclusion of all students.